Another day, another tennis coaching intervention, but does this one do what coaches purport? - Reid, M.; Giblin, G. (Sports Biomechanics, 2015)
A proficient serve is critical to successful tennis performance, and consequently coaches and players devote considerable time refining this stroke. In so doing, a wide variety of interventions are used or trialled, generally with very little empirical support. This study examined the efficacy of a commonly used service intervention, where players focus on exaggerating their finish (arabesque) position to promote specific changes in lower limb and trunk kinematics. The kinematics of eight high-performance junior players hitting flat serves were compared to the acute changes in kinematics elicited by the arabesque follow through position on serves using a 10-camera VICON MX motion analysis system. The significantly greater front (landing leg) hip flexion (p < 0.05) and forward trunk flexion (p < 0.05) confirmed the more exaggerated arabesque landing position following the arabesque instruction. The arabesque instruction resulted in increased frontal plane trunk range of motion and peak angular velocity in the forward swing, and increased leg drive during the drive phase. Practically, the results support the use of the arabesque instruction, effectively promoting the desired acute changes in trunk kinematics (i.e. increased frontal plane trunk rotation angular velocity) and leg drive (i.e. increased back knee extension angular velocity and front/back vertical hip velocity).